1980
DOI: 10.1113/jphysiol.1980.sp013495
|View full text |Cite
|
Sign up to set email alerts
|

Amylase release from dissociated mouse pancreatic acinar cells stimulated by glucagon: effect of membrane stabilizers.

Abstract: SUMMARY1. The effect of membrane stabilizers and cytochalasin-B on amylase secretion, basal and induced by ionophore A23187, CCK-PZ, bethanechol and glucagon, was studied in dissociated mouse pancreatic acinar cells.2. Cytochalasin-B did not affect basal or secretagogue-stimulated amylase secretion.3. Membrane stabilizers [thymol (10-7-104 M), chlorpromazine (I0-7-1 04 M) and propranolol (10-7-10-5 M) did not alter basal release of amylase. At higher concentrations of thymol (10-3 M), chlorpromazine (10-3 M) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

1982
1982
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
2
10
1
Order By: Relevance
“…Unlike contraction, exocytosis involves complex membrane interactions -and cell membranes are a classic site of action of neuroleptic drugs which not only block ion channels and receptors for various autacoids but additionally have ' unspecific' effects on membranes that include ' stabilization', 'destabilization' and displacement of membrane-bound Ca (Seeman, 1972;Lullman et al 1980). Indeed, such unspecific membrane effects have been commonly invoked to explain effects of these drugs on exocytosis and on membrane fusion-fission processes in general (see, for example, Poste & Allison, 1973;Williams et al 1977;Elferink, 1979;Singh, 1980). Nevertheless, our results indicate some other, more specific, action.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Unlike contraction, exocytosis involves complex membrane interactions -and cell membranes are a classic site of action of neuroleptic drugs which not only block ion channels and receptors for various autacoids but additionally have ' unspecific' effects on membranes that include ' stabilization', 'destabilization' and displacement of membrane-bound Ca (Seeman, 1972;Lullman et al 1980). Indeed, such unspecific membrane effects have been commonly invoked to explain effects of these drugs on exocytosis and on membrane fusion-fission processes in general (see, for example, Poste & Allison, 1973;Williams et al 1977;Elferink, 1979;Singh, 1980). Nevertheless, our results indicate some other, more specific, action.…”
Section: Discussioncontrasting
confidence: 50%
“…It 240 W. W. DOUGLAS AND E. F. NEMETH is sufficient to explain the inhibition of responses to 48/80, which was acheived with similar concentrations of each of the drugs; but an additional component seems to contribute to the inhibition of responses to antigen since the drugs were active in lower concentration and in a somewhat different rank order of potency. Because antigen, unlike 48/80, acts mainly by opening membrane Ca channels, this may be the process that is additionally affected; neuroleptic drugs inhibit stimulus-induced Ca influx in various other secretary cells (see Williams et al 1977;Singh, 1980;Fleckman, Erlichman, Schubart & Fleischer, 1981;Valverde, Sener, Lebrun, Herchuelz & Malaisse, 1981) and smooth muscles (see Chaturvedi, Landon & Rama Sastry, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies it has been reported that the effect of Som on pancreatic amylase output could be inhibitory or stimulatory, or there might be no effect, depending on whether it was an in vivo or an in vitro study, the concentration of Som or the species of animal (Holst, 1993;Owyang, 1993;Adeghate et al 1997). In contrast, Glu evoked a monophasic secretory response similar to results obtained in previous studies (Singh, 1980;Pandol et al 1983;Adeghate et al 1997). The concentrations of Som or Glu employed in this study have previously been shown to elicit only small increases in amylase secretion (Pandol et al 1983;Owyang, 1993;Adeghate et al 1998).…”
Section: Immunohistochemistrysupporting
confidence: 48%
“…This potentiatory action of Ins on ACh-evoked enzyme secretion is believed to be associated with the mobilization of cellular Ca¥ and cAMP metabolism (Singh, 1983(Singh, , 1985bJuma et al 1997a) and zymogen granular regulatory protein phosphorylation (Burnham & Williams, 1982;Williams & Goldfine, 1993). Glu on its part has been shown to increase amylase secretion from dissociated pancreatic acinar cells (Singh, 1980;Pandol et al 1983). The effect of Som on pancreatic amylase secretion has not been throughly investigated and moreover, the role of islet hormones such as Glu and Som in the control of pancreatic enzyme secretion and their interaction with the classical secretagogue CCK in normal and diabetic animals are not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…Many chemicals that are volatile and lipophilic, physicochemical properties shared by thymol, have anaesthetic effects in humans; furthermore, at therapeutic concentrations, ion channels are the principal targets of anaesthetics (Yamakura et al, 2001), but for many years this was thought to be an indirect action secondary to bilayer disordering, for example, detergents and free fatty acids affect receptor channel function in this way (Koenig & Martin, 1992). Thymol is known to affect plasma membrane properties such as stability (Singh, 1980;Manabe et al, 1987) and permeability to drugs, for example, piroxicam (Doliwa et al, 2001). In our study, thymol did not affect bilayer integrity at the concentrations required for potentiation, as negligible changes in the current required to clamp the membrane potential (o10 nA) occurred in uninjected oocytes.…”
Section: CM Priestley Et Almentioning
confidence: 99%